The Attitudes of Czech Teachers Towards the Use of Artificial Intelligence in Schools - Lucie Zormanová (Jesuit University Ignatianum in Krakow, 2024)
RESEARCH OBJECTIVE: The objective of this research study was to find out the subjective feelings of Czech teachers regarding the introduction of artificial intelligence into schools. THE RESEARCH PROBLEM AND METHODS: The following research questions follow from the research objective: Are Czech teachers worried about the introduction of artificial intelligence into schools? Do Czech teachers see artificial intelligence as a tool that will help them? Do Czech teachers have experience with the use of artificial intelligence? What experience do teachers have with artificial intelligence? To achieve the research objective and answer the research questions, the in-depth interview method with primary and secondary school teachers was used. THE PROCESS OF ARGUMENTATION: The first part of the article discusses the concept of artificial intelligence. The second part discussed the use of artificial intelligence in Czech schools. The third part presents the results of a research study was to find out the subjective feelings of Czech teachers regarding the introduction of artificial intelligence into schools. RESEARCH RESULTS: As part of the research, it was found that some teachers are concerned about the advent of artificial intelligence and its use in education, especially that students will "misuse" AI to cheat and plagiarize. Most teachers see the application of artificial intelligence in schools as inevitable and realize that it is their task to teach students to use AI effectively. Teachers are also aware that with the implementation of AI into schools, the teaching system will also have to change. CONCLUSIONS, RECOMMENDATIONS AND APPLICABLE VALUE OF RESEARCH: We can expect that teachers will consider artificial intelligence as a tool that helps them and makes their work easier. A big impetus will be the integration of artificial intelligence into tools that teachers commonly work with, such as Office 365 or Google Workspace.